Oxygen consumption efficiency in firefighters: roles of fatigue and rescue task - Zhang, Xinxin; Li, Chengxiu; Zhou, Yong; Liu, Weiguo (Frontiers in Physiology, 2025)
ObjectiveThis study compared standardized oxygen consumption responses during rescue tasks with varying loads and methods across different fatigue states in firefighters to identify optimal rescue strategies and enhance operational efficiency.MethodsSixty-three professional healthy male firefighters were recruited. Oxygen consumption was measured using a wearable metabolic system as they performed 5 × 20-m shuttle sprints with different task loads (10 kg, 20 kg, 30 kg) and rescue methods (shoulder-, cradle-, hand-carrying) under five fatigue states (non-fatigue, whole-body, and mild/moderate/severe knee fatigue).ResultsA mixed-model ANOVA revealed a significant main effect of task load on standardized oxygen consumption (F = 620.61, P < 0.001, ƞp2 = 0.798). Post-hoc tests showed that standardized oxygen consumption was significantly lower during medium-load (2.464 ± 0.616 mL/min/kg2) and large-load tasks (1.615 ± 0.317 mL/min/kg2) compared to small-load tasks (4.718 ± 1.043 mL/min/kg2) (all P < 0.05). Consumption during large-load tasks was also significantly lower than during medium-load tasks (P < 0.05). The main effects of fatigue states and rescue methods were not significant.ConclusionTask load is the primary factor influencing oxygen efficiency during high-intensity shuttle sprints. Large-load tasks resulted in significantly lower standardized oxygen consumption across all fatigue states and rescue methods, indicating a “small load-low efficiency” phenomenon. Prioritizing large-load (30 kg) tasks in time-critical emergencies may improve rescue efficiency.